Faktor yang berhubungan dengan Keluhan Low Back Pain (LBP) pada Pekerja Perajin Batu Bata di Kabupaten Seluma - Andriana Marwanto; Agus Widada; Riang Adeko; Prasetyawati Prasetyawati (Poltekkes Kemenkes Maluku, 2021)
Occupational health absolutely must be implemented in work, both informal and formal industries. Activities that can cause health problems are improper work attitudes such as sitting, standing, bending, squatting, walking, and others. Health problems related to work attitudes are complaints of low back pain (LBP). This type of research is a descriptive-analytic study with a cross-sectional approach. Research respondents are brick workers in Babatan Seluma Village with 60 workers. Data were obtained by interviewing the respondents' characteristics, years of service, work attitudes, and complaints of LBP. Data analysis was carried out using the Chi-Square test to determine the relationship between variables and the logistic regression test to determine the factors most at risk for the occurrence of complaints. The results showed that 51.70% of the respondents were less than 40 years old, the respondent's working period of more than 10 years was 51.80%, and most of the respondents (56.70%) had non-ergonomic work attitudes. This study shows a relationship between age, tenure, and work attitude towards LBP complaints with a p-value (0.040; 0.050; 0.016). Workers are expected to work according to an ergonomic work attitude to avoid LBP complaints.